1, 4-naphthoquinone efficiently facilitates the disintegration of pre-existing biofilm of Staphylococcus aureus through eDNA intercalation - Paul, Payel; Sarkar, Sarita; Dastidar, Debabrata Ghosh; Shukla, Aditya; Das, Sharmistha; Chatterjee, Sudipta; Chakraborty, Poulomi; Tribedi, Prosun (Folia microbiologica, 2023)
1, 4-naphthoquinone, a plant-based quinone derivative, has gained much attention for its effectiveness against several biofilm-linked diseases. The biofilm inhibitory effect of 1, 4-naphthoquinone against Staphylococcus aureus has already been reported in our previous study. We observed that the extracellular DNA (eDNA) could play an important role in holding the structural integrity of the biofilm. Hence, in this study, efforts have been directed to examine the possible interactions between 1, 4-naphthoquinone and DNA. An in silico analysis indicated that 1, 4-naphthoquinone could interact with DNA through intercalation. To validate the same, UV-Vis spectrophotometric analysis was performed in which a hypochromic shift was observed when the said molecule was titrated with calf-thymus DNA (CT-DNA). Thermal denaturation studies revealed a change of 8°C in the melting temperature (Tm) of CT-DNA when complexed with 1, 4-naphthoquinone. The isothermal calorimetric titration (ITC) assay revealed a spontaneous intercalation between CT-DNA and 1, 4-naphthoquinone with a binding constant of 0.95 ± 0.12 × 108. Furthermore, DNA was run through an agarose gel electrophoresis with a fixed concentration of ethidium bromide and increasing concentrations of 1, 4-naphthoquinone. The result showed that the intensity of ethidium bromide-stained DNA got reduced concomitantly with the gradual increase of 1, 4-naphthoquinone suggesting its intercalating nature. To gain further confidence, the pre-existing biofilm was challenged with ethidium bromide wherein we observed that it could also show biofilm disintegration. Therefore, the results suggested that 1, 4-naphthoquinone could exhibit disintegration of the pre-existing biofilm of Staphylococcus aureus through eDNA intercalation.
Keywords: Ethidium; Staphylococcus aureus; ethidium; Staphylococcal Infections; DNA; lidé; biofilmy; stafylokokové infekce; Naphthoquinones; naftochinony; Biofilms; Humans